Photodegradation of Commercial Dye 920 DB2 Using TiO2 - Mahdi, Amel S (Al-Nahrain Journal of Science, 2018)
Photo decomposition of 920 (DB2) dye have been performed at (nm) in deionized water at 25C˚.Under irradiation Uv Lamp. The absorbance spectrum for this dye have been recorded with the time of irradiation in order to examine the kinetics of photo decay. The specific rate constant the (Kd) for the first order reaction have been calculated and found to be (Kd = 0.0248 min-1). Study the effect of various parameters such as catalyst loading, pH of the medium and initial dye concentration. On photodecomposition of 920 (DB2)